Validation of the Partners at Care Transitions Measure (PACT-M): assessing the quality and safety of care transitions for older people in the UK - Eirini Oikonomou; Bethan Page; Rebecca Lawton; Jenni Murray; Helen Higham; Charles Vincent (BMC, 2020)
Abstract Background The Partners at Care Transitions Measure (PACT-M) is a patient-reported questionnaire for evaluation of the quality and safety of care transitions from hospital to home, as experienced by older adults. PACT-M has two components; PACT-M 1 to capture the immediate post discharge period and PACT-M 2 to assess the experience of managing care at home. In this study, we aim to examine the psychometric properties, factor structure, validity and reliability of the PACT-M. Methods We administered the PACT-M over the phone and by mail, within one week post discharge with 138 participants and one month after discharge with 110 participants. We performed principal components analysis and factors were assessed for internal consistency, reliability and construct validity. Results Reliability was assessed by calculating Cronbach's alpha for the 9-item PACT-M 1 and 8-item PACT-M 2 and exploratory factor analysis was performed to evaluate dimensionality of the scales. Principal components analysis was chosen using pair-wise deletion. Both PACT-M 1 and PACT-M 2 showed high internal consistency and good internal reliability values and conveyed unidimensional scale characteristics with high reliability scores; above 0.8. Conclusions The PACT-M has shown evidence to suggest that it is a reliable measure to capture patients' perception of the quality of discharge arrangements and also on patients' ability to manage their care at home one month post discharge. PACT-M 1 is a marker of patient experience of transition and PACT-M 2 of coping at home.